Peripheral Vascular Dysfunction in Chronic Kidney Disease - Christopher R. Martens; David G. Edwards (Cardiology Research and Practice)
There is an increased prevalence of cardiovascular disease- (CVD-) related mortality in patients with chronic kidney disease (CKD). Endothelial dysfunction is a primary event in the development of atherosclerosis and hypertension and likely contributes to the elevated cardiovascular risk in CKD. Endothelial dysfunction has been shown to occur in the peripheral vasculature of patients with both severe and moderate CKD. Mechanisms include oxidative stress, L-arginine deficiency, and elevated plasma levels of ADMA. Interventions designed to restore vascular function in patients with CKD have shown mixed results. Evidence from cell culture studies suggest that the accumulation of uremic toxins inhibits L-arginine transport and reduces nitric oxide production. The results of these studies suggest that endothelial dysfunction may become less reversible with advancing kidney disease. The purpose of this paper is to present the current literature pertaining to potential mechanisms of peripheral vascular dysfunction in chronic kidney disease and to identify possible targets for treatment.